Effects of salt water intrusion on biochemical components of Alder and Ash tree fresh leaves in Karacabey Coastal Forested Wetland - Sarıyıldız, Temel; Alı, Raghad Samı Sahıb Mohammed (My University, 2023)
Coastal forested wetlands provide substantial benefits to society, such as wave attenuation, erosion control, biodiversity support, and carbon sequestration. Many of these unique coastal ecosystems have been drained for various reasons, while those that remain are now threatened by salt water intrusion and sea level rise due to climate change. In this study, we aimed to investigate the effects of soil salinity on the biochemical components of the fresh leaves of alder (Alnus glutinosa L. Gaertn) and ash tree (Fraxinus angustifolia Vahl.) which are the dominant tree species in Karacabey coastal forested wetland next to the Sea of Marmara in Türkiye. For this purpose, fresh leaf and soil samples of alder and ash trees were collected from three zones (Z1: 0-1 km, Z2: 1 to 2 km and Z3: 2 to 3 km) from the inner border (Z3) of the forested wetland to the coastline (Z1) of the Sea of Marmara. The fresh leaf samples were analyzed for photosynthetic pigments (chlorophyll a, chlorophyll b and carotenoids), anthocyanin, xanthophylls, free amino acids, total nitrate, proline, total polyphenols, total soluble tannins, total phenolic compounds, glucose, sucrose and total carbohydrates. The soil samples were analyzed for soil pH, electrical conductivity and soil texture. The results showed that the soil salinity decreased from the coastline (Z1) towards the inner border (Z3). Similarly, mean photosynthetic pigments and anthocyanin, xanthophyll also decreased from the Z1 towards Z3, whereas mean total polyphenols and total soluble tannin concentrations increased for the both tree species. The other biochemical compounds showed either an increase or a decrease according to the tree species. These pioneer results illustrate the important point that biotic or abiotic environment in which tree grows significantly change the specific biochemical components in the fresh leaves of alder and ash trees in the coastal forested wetlands. In turn, these changes may result in variation in nutrient cycling, carbon cycling, and organic matter turnover rates in these forest ecosystems.
Keywords: Türkiye; Alnus glutinosa; Fraxinus angustifolia; Fotosentetik pigmentler; Toprak tuzluluğu